PENGARUH KEPEMILIKAN MANAJERIAL, LEVERAGE, DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Elsya Manora Manurung; Deannes Isynuwardhana (JAF (Journal of Accounting and Finance), 2017)
Earnings management can be defined as a deliberate intervention by management in determining the profit in the process of preparation of financial reporting, in order to gain personal profit. The existence cases earnings management not only the make the company concerned went bankrupt, but Also resulted in the perpetrators are punished as perpetrators of economic crimes, indication of earnings management by the news media that the capacity of the financial statements to report financial information to various parties become less relevant. This research aims is to analyze the effect factors that include ownership managerial, leverage and profitabilitas to earnings management. This research methode uses is quantitative research method which is classified to causality verificative descriptive research. Population research is company mining sector registered at the indonesian stock exchange ( IDX ) periode 2013 to 2015, There are 24 mining companies included, and 72 data processed. Data process is taken from secondary data, Method analysis data is regression panel data using eviews program versi 8.0. The result show that there are significant influence between managerial ownership, leverage and profitability with earning management either simultaneously. Partially, ownership managerial and leverage have no significant effect on earning management. While Probability has significant positif effect on earnings management